Financial Performance of Hospitals in the Appalachian Region Under the Hospital Readmissions Reduction Program and Hospital Value‐Based Purchasing Program - Karim, Saleema A.; Nevola, Adrienne; Morris, Michael E.; Tilford, J. Mick; Chen, Hsueh‐Fen (The Journal of rural health, 2021)
Purpose The Hospital Readmission and Reduction Program (HRRP) and Hospital Value‐Based Purchasing Program (HVBP) propose to improve quality of patient care by either rewarding or penalizing hospitals through inpatient reimbursement. This study analyzes the effect of both programs on profitability of hospitals located in the Appalachian Region (AR) compared to hospitals in Appalachian states and the rest of the United States. Methods This study used a retrospective research design with a longitudinal unbalanced panel dataset from 2008 to 2015. Hospitals participating in both HRRP and HVBP during this time frame were included in the study. A difference‐in‐difference model with hospital‐level fixed effects, controlling for hospital and market characteristics, was used to determine effects of both programs on profitability of hospitals serving the AR, Appalachian states, and the rest of the United States. Findings After implementation of HRRP and HVBP, only hospitals located in Appalachian states experienced a significant decrease in operating margin (−1.14 percentage points). Unexpectedly, during the same time period, total margin increased significantly for hospitals located in the AR (1.05 percentage points), Appalachian states (1.71 percentage points), and the rest of the United States (2.38 percentage points). Conclusions HRRP and HVBP financially incentivize hospitals to focus efforts on improving patient care. The programs may not have the anticipated results. Increases in total margin for all hospitals during the study period indicate access to nonpatient revenues, offsetting the financial penalties from both programs. This revenue source may undermine the program's objectives of delivering value and achieving quality outcomes.